Patterns of MHC-dependent mate selection in humans and nonhuman primates: a meta-analysis - Winternitz, J; Abbate, J L; Huchard, E; Havlíček, J; Garamszegi, L Z (Molecular ecology, 2017)
Genes of the major histocompatibility complex (MHC) in vertebrates are integral for effective adaptive immune response and are associated with sexual selection. Evidence from a range of vertebrates supports MHC-based preference for diverse and dissimilar mating partners, but evidence from human mate choice studies has been disparate and controversial. Methodologies and sampling peculiarities specific to human studies make it difficult to know whether wide discrepancies in results among human populations are real or artefact. To better understand what processes may affect MHC-mediated mate choice across humans and nonhuman primates, we performed phylogenetically controlled meta-analyses using 58 effect sizes from 30 studies across seven primate species. Primates showed a general trend favouring more MHC-diverse mates, which was statistically significant for humans. In contrast, there was no tendency for MHC-dissimilar mate choice, and for humans, we observed effect sizes indicating selection of both MHC-dissimilar and MHC-similar mates. Focusing on MHC-similar effect sizes only, we found evidence that preference for MHC similarity was an artefact of population ethnic heterogeneity in observational studies but not among experimental studies with more control over sociocultural biases. This suggests that human assortative mating biases may be responsible for some patterns of MHC-based mate choice. Additionally, the overall effect sizes of primate MHC-based mating preferences are relatively weak (Fisher's Z correlation coefficient for dissimilarity Zr = 0.044, diversity Zr = 0.153), calling for careful sampling design in future studies. Overall, our results indicate that preference for more MHC-diverse mates is significant for humans and likely conserved across primates.
Keywords: Mating Preference, Animal; manželství; Animals; Genetics, Population; sexuální výběr u zvířat; lidé; HLA; hlavní histokompatibilní komplex; good genes; mating preference; Major Histocompatibility Complex; Marriage; Humans; major histocompatibility complex; sexual selection; populační genetika; inbreeding avoidance; zvířata